Rancang Bangun Sistem Pengolahan Citra Digital untuk Menentukan Berat Badan Ideal - Toni Efendi; Tsurayya Ats Tsauri; Iin Intan Uljanah (JISKA (Jurnal Informatika Sunan Kalijaga), 2017)
In actual fact, there are many people who do not know whether their weight have been ideal or not due to unavailable device or machine that can be used to measure ideal weight practically. Therefore, in order to measure the ideal weight practically, the researcher is attempting to create a system based on image processing which is developed by using Matlab software. As a preliminary step, the researcher collects some samples data that will be used in the research. Furthermore, the calculation formula is analysed by the researcher to be used in the system. This research is using a formula namely Body Surface Area (BSA) with a tubular analogy of human body. Image processing is made by using the edge detection algorithm to know the height and width of objects in an image of the human body. In addition, by certain search algorithm the height and width of object in the image of human body will be known and used for measuring approximate height and weight. Besides, Body Mass Index (BMI) formula is used for measuring ideal weight. the research shows that the value of the average percentage difference deviation of the system is 1.63% for height and 11.6% for weight. At least but not last, for the level of system accuracy reaching up to 75% of the body actual condition by system calculating result.